Secado con bomba de calor para la deshidratación de frtutas - Zavala Cerna, Orlando Alfredo (2013)
This study evaluated the performance of the drying rate of the pulp of banana and apple using indirect drying. The experiments were performed using a dryer with heat cabinet at laboratory level. Banana variety was used: type silk tropical (jungle) and type apple variety tropical delight (Huaral). Measurements were made of the variables of interest, dry and wet temperature at the inlet and outlet of the equipment, air velocity and humidity loss, these curves allowed for drying, obtaining an efficiency of the drying of pulp banana and apple pulp 73%, concluding that direct drying is more efficient but costs increase, while dehydration heat pump are lower. Drying kinetics in both systems the difference in drying time